Synthesis, Characterization and DFT Studies on Some 2,3-Dihydro-4-Methyl-1H-1,5-Benzodiazepinone and N-Isopropenyl Benzimidazolone Derivatives - Soleiman, Hussain Ali; Said, Ridha Ben; Alayed, Abdallah Suliman (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
Benzodiazepinones and benzimidazolones have been synthesized by the reaction of o-phenylenediamine with ethylacetoacetate in boiling xylene. Alkylation of the obtained compounds was carried out by reaction with excess of ethyl iodide. The reaction of alkylated compounds with aromatic aldehyde leads to the formation of aryldinodiazepinone and/or arylidinone derivatives. The prepared compounds were tested for antibacterial and fungicidal activity. Gram-negative bacteria (Bacillus cereus), as well as the fungus was used for this purpose. The newly prepared compounds have been characterized by IR, MS, elemental analysis and 1H NMR spectroscopies and as well as theoretical level (DFT/B3LYP).